Bubbles in experimental asset markets: Irrational exuberance no more - Lucy F. Ackert; Bryan K. Church; Richard Deaves (Federal Reserve Bank of Atlanta, 2002)
The robustness of bubbles and crashes in markets for finitely lived assets is perplexing. This paper reports the results of experimental asset markets in which participants trade two assets. In some markets, price bubbles form. In these markets, traders will pay even higher prices for the asset with lottery characteristics, i.e., a claim on a large, unlikely payoff. However, institutional design has a significant impact on deviations in prices from fundamental values, particularly for an asset with lottery characteristics. Price run-ups and crashes are moderated when traders finance purchases of the assets themselves and are allowed to short sell.
Keywords: 330; Financial markets; Risk